Analisis Asuhan Keperawatan dengan Intervensi Terapi Aktivitas Kelompok pada Pasien dengan Masalah Keperawatan Halusinasi Pendengaran - Wulandari, Ni Kadek Ayu Desi Dian; Heri, Mochamad; Putra, G. Nur Widya; Astriani, Ni Made Dwi Yunica; Dewi, Putu Indah Sintya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the analysis of nursing care using group activity therapy for patients with hallucinations. This research method uses a descriptive research design in the form of a case study that identifies a nursing care problem for patients with mental disorders, such as auditory hallucinations. The intervention results were based on the diagnosis, including building a relationship of mutual trust and SP2 to SP3. An additional intervention was given, namely the TAK Stimulation of Perception (Self Care Deficit) activity, which was carried out for two sessions. In conclusion, the difference in the ability to control hallucinations before giving group activity therapy compared to after giving group activity therapy is in the form of a continuous accumulation of increasing previous knowledge. Keywords: Auditory Hallucinations, Schizophrenia, Group Activity Therapy